(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article presented reflections based on the author’s experience with drama in education in elementary schools in the city of Uberlândia, Minas Gerais (Brazil). The guiding question was: what challenges and possibilities emerged when considering the drama in education? Based on processes carried out with children, teenagers and youth, the assay discussed the principles of drama, its implementation in daily school life, and the challenges faced. Strategies, conventions, and artistic and pedagogical possibilities were highlighted, with an emphasis on collective creation and active listening to school contexts.